Analisis Bibliometrik Perkembangan Penelitian Material Flow Cost Accounting (MFCA) Berdasarkan Data Scopus - Zul Azmi; Suraya Nadella; Della Apriliana (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Material Flow Cost Accounting (MFCA) is an environmental management accounting approach that aims to improve material efficiency while reducing environmental impact. This study aims to analyze the development of scientific publications related to MFCA through a bibliometric literature review. Data were collected using the Scopus database using the keyword "Material Flow Cost Accounting" in the Title-Abstract-Keywords section. All relevant publications were then tabulated and analyzed descriptively to identify annual publication trends, major contributing countries, most cited articles, and subject areas. The results show that publications on MFCA began appearing in 2006 and experienced a significant increase in 2015. Germany and China were the countries with the largest publication contributions, while the most highly cited articles on the topic of MFCA were generally published in the Journal of Cleaner Production. Overall, these findings indicate that MFCA has developed into a vital part of the scientific discourse on sustainable accounting and resource efficiency and still holds potential for further research, especially in the context of developing countries like Indonesia.